On first and second-order perturbed differential inclusions governed by maximal monotone operators - Benguessoum, Messaouda; Azzam-Laouir, Dalila (Topological Methods in Nonlinear Analysis, 2024)
In this paper we establish, in a separable Hilbert space, a resultasserting the existence of absolutely continuous solutions for asystem made up of a first-order differential inclusion governed bytime and state-dependent maximal monotone operators; and an ordinarydifferential equation. From this result, we derive existence ofabsolutely continuous solutions to a second-order differentialinclusion governed by time and state-dependent maximal monotoneoperators.